Report on the Antiquties found in Scotland, and preserved in the British Museum, &c., London, and in the Museum of Science and Art, Edinburgh; obtained under the Jubilee Gift of His Excellency Dr. R. H. Gunning, F.S.A. Scot - Black, George F (Proceedings of the Society of Antiquaries of Scotland, 1893)